1992
DOI: 10.1039/fd9929400107
|View full text |Cite
|
Sign up to set email alerts
|

Underpotential deposition and electrocrystallization of metals: an in situ scanning tunnelling microscopy study with lateral atomic resolution

Abstract: The formation of well ordered 2D metal adsorbate layers in the underpotential range and 3D metal deposits in the overpotential range on foreign substrates has been studied in the model system Ag(hkl)/Pb2+ by in situ scanning tunnelling microscopy (STM) under defined potential control with lateral atomic resolution. The results are compared to electrochemical, morphological, in situ EXAFS and GIXS investigations. In situ STM provides an excellent atomic view of the initial steps of underpotential deposition (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Since CH 3 COO - is expected to be more strongly adsorbed than ClO 4 - , the absence of the A 1 /C 1 and A 3 /C 3 waves in CH 3 COO - solutions has been associated with blocking of the step edges by CH 3 COO - anions. In-situ STM imaging of the Ag(111) surface during upd of Pb supports this hypothesis. , The fact that we observe a more ideal voltammetric response and greatly diminished A 1 /C 1 and A 3 /C 3 waves in ClO 4 - solutions, while also observing a very broad wave in CH 3 COO - solutions, suggests that the nucleation and growth of a Pb upd layer may be accelerated by surface defect structures. This conclusion is supported by the observation that while the voltammetric wave shape in ClO 4 - solutions is rather insensitive to the scan rate, the voltammetric response in CH 3 COO - becomes more irreversible as the scan rate is increased.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Since CH 3 COO - is expected to be more strongly adsorbed than ClO 4 - , the absence of the A 1 /C 1 and A 3 /C 3 waves in CH 3 COO - solutions has been associated with blocking of the step edges by CH 3 COO - anions. In-situ STM imaging of the Ag(111) surface during upd of Pb supports this hypothesis. , The fact that we observe a more ideal voltammetric response and greatly diminished A 1 /C 1 and A 3 /C 3 waves in ClO 4 - solutions, while also observing a very broad wave in CH 3 COO - solutions, suggests that the nucleation and growth of a Pb upd layer may be accelerated by surface defect structures. This conclusion is supported by the observation that while the voltammetric wave shape in ClO 4 - solutions is rather insensitive to the scan rate, the voltammetric response in CH 3 COO - becomes more irreversible as the scan rate is increased.…”
Section: Resultssupporting
confidence: 72%
“…The initial investigations of Pb upd at Ag(111) by Bewick and Thomas suggested that the above voltammetric response corresponds to the deposition of ∼1 monolayer of Pb. , More recent in-situ grazing incidence X-ray diffraction (GIXS) measurements have demonstrated that the completed Pb upd layer is a closed-packed structure, rotated from the Ag(111) surface by ∼4.5°. This structure has been recently confirmed by in-situ STM , for the same solution conditions and will be assumed in the discussion below.…”
Section: Resultsmentioning
confidence: 83%
“…Much work has attended studies of Pb upd on Ag surfaces. STM work on Ag(111) [144][145][146] demonstrated that the full monolayer in this system also gave rise to a (1×1) monolayer which, like its counterpart on Au(111) also formed a moire ´pattern. Detailed analysis on this pattern allowed the authors to discern the degree of rotation (ca.…”
Section: Silver Surfacesmentioning
confidence: 86%
“…By far, the most studied UPD system on silver single crystals has been lead deposition. This process has been studied by a wide variety of techniques including electrochemical, , optical reflectivity, SHG, STM, ,, X-ray absorption spectroscopy, X-ray scattering, and UHV techniques such as low-energy electron diffraction and Auger electron spectroscopy. ,, Theoretical models of lead deposition on silver single crystals have also been proposed and studied. …”
Section: Upd On Silver Surfacesmentioning
confidence: 99%